Sintesis Hijau Nanopartikel Perak menggunakan Ekstrak Eceng Gondok sebagai Agen Bioremediasi Pengolahan Air Limbah - Salman Farisi; Enur Azizah; Primasari Pertiwi (KLOROFIL: Jurnal Ilmu Biologi dan Terapan, 2025)
Water pollution in Lampung mostly caused by domestic waste. The proposed solution in dealing with these problems is the use of silver nanoparticles (AgNP) as a potential bioremediation agent with water hyacinth. The use water hyacinth in AgNP synthesis can help reduce weed populations and domestic waste contaminants in water that causes eutrophication. The AgNP synthesis process begins with the preparation of water hyacinth which is extracted and filtered using Whatman No. 42. The filtrate is then reacted with 2 mM AgNO3 solution and analyzed with FT-IR and SEM. After AgNP were formed, effectiveness was tested on polluted water with AgNP concentration variations of 1:1, 1:2, 1:3 and 1:4. The effectiveness of AgNP was assessed through pH, BOD5 and TSS. The result of the analysis showed that the higher the concentration of AgNP, the higher decrease in BOD5 and TSS value, as well as the improvement in pH values. These test results were supported by ANOVA analysis which showed a significant effect of AgNP concentration on pH, BOD5 and TSS.